The effects of maternal Yoga and Self-compassion exercises on behavioral disorders and depression of Disabled Children - Azam Lotfi jebeli; Zohreh Meshkati (Shiraz University of Medical Sciences, 2021)
Background: The purpose of the present study was tocompare the effects of maternal yoga and self-compassion exercises on behavioral disorders and depression of children with disabilities. Methods: This applied research is a quasi-experimental study with pre-test-post-test control group design. The participants of the current research consisted of 40 cases of mothers (with an average age of 29 years) of disabled children aged 6-18, who were selected using convenience sampling method from Welfare Centers in Isfahan city, and were matched into three experimental groups, and one control group based on depression scores. In order to assess the behavioral disorders and depression in children with disabilities, Child Behavior Checklist (CBCL, Achenbach) and Children Depression Inventory (CDI, Maria Kovacs) were used, respectively. Data were analyzed using univariate and multivariate analysis of covariance at a significance level of α ≤0.05. Results: The obtained results showed that the pre-test scores of behavioral disorders have a significant relationship with its post-test. When this relationship was controlled, the difference between adjusted means of behavioral disorders scores in the post-test stage in intervention groups was significant. Additionally, no significant relationship was observed between the pre-test and post-test scores of depression, but the difference between adjusted means of depression scores in the post-test stage (after controlling pre-test scores) in intervention group was significant. Conclusion: Practicing yoga and self-compassion exercises by mothers can cause a reduction in behavioral disorders and depression in children with disabilities. These results show that the family of disabled children, welfare organization, exceptional schools and rehabilitation centers can consider paying attention to parental mental health.